(untitled) (Journal of Nematode Morphology and Systematics, 2012)
The taxonomic lineage of the nematode currently known as Panagrellus redivivus can be traced, through numerous generic assignments and species synonymies, to the library paste nematode, Chaos redivivum, described by Linnaeus in 1767. In a synonymy that has survived several reviews, the beer mat nematode, described by de Man in 1913 and 1914, is now considered to be the same as the library- or sour-paste nematode. In the absence of preserved specimens of early material, and with the inadequacy of early descriptions of the organisms, the unifying thread for the taxonomic lineage is the nature of the environments in which the nematodes have been found, primarily fermenting pastes and beer-soaked fibres that might provide substrate for yeasts. Consequently, despite the precise rules that have evolved for documenting changes in a binomial, and our ability to track those changes through the literature, there must remain lingering uncertainty that Chaos redivivum and Panagrellus redivivus are the same nematode.